A Perfect Storm in the Amazon Wilderness Success and Failure in the Fight to Save an Ecosystem of Critical Importance to the Planet (Volume 1-72) - Killeen, Timothy J. (The White Horse Press, 2021)
This is the first chapter in Timothy Killeen's meticulously researched two-volume study of the challenges facing the fight to preserve the Amazon rainforest. A comprehensive work that will be essential reading for anyone with an interest in this critically important subject.